Piston ring assembly for a new natural gas vehicle symmetrical multistage wobble-plate compressor - Arafat, Andril (2006)
Natural gas is an alternative fuel of choice in the market today due to the increase in the price of petroleum, as well as out of environmental concerns. Pressure requirement for a natural gas vehicle (NGV) storage tank is 3000 psig (206 bars). Thus, at NGV refueling facilities, the natural gas need to be stored at a higher pressure in order to refuel the NGV at the pressure required. Compressors are needed in the compression process at the refueling facilities. A new compressor design for natural gas refueling appliance has been developed which is the symmetrical multistage wobble-plate compressor. This compressor design is the newest variation of the axial reciprocating piston compressor. The success of the compressor design in compressing gas depends on the piston ring assembly design. Through this paper, the process of designing the piston ring assembly and considerations taken for this new compressor design were explained. The results presented are those from preliminary tests using air on the working fluid. Real tests on natural gas are to be organised utilising all the experience and lesson learnt from that on air.